Effects of two different paradigms of electrical stimulation exercise on cardio-metabolic risk factors after spinal cord injury. A randomized clinical trial - Gorgey, Ashraf S.; Khalil, Refka E.; Carter, William; Ballance, Boyd; Gill, Ranjodh; Khan, Rehan; Goetz, Lance; Lavis, Timothy; Sima, Adam P.; Adler, Robert A. (Frontiers in Neurology, 2023)
Objective To examine the combined effects of neuromuscular electrical stimulation-resistance training (NMES-RT) and functional electrical stimulation-lower extremity cycling (FES-LEC) compared to passive movement training (PMT) and FES-LEC in adults with SCI on (1) oxygen uptake (VO2), insulin sensitivity and glucose disposal in adults with SCI; (2) Metabolic and inflammatory biomarkers; (3) skeletal muscle, intramuscular fat (IMF) and visceral adipose tissue (VAT) cross-sectional areas (CSAs). Materials and methods Thirty-three participants with chronic SCI (AIS A-C) were randomized to 24 weeks of NMES-RT + FES or PMT + FES. The NMES-RT + FES group underwent 12 weeks of evoked surface NMES-RT using ankle weights followed by an additional 12 weeks of progressive FES-LEC. The control group, PMT + FES performed 12 weeks of passive leg extension movements followed by an additional 12 weeks of FES-LEC. Measurements were performed at baseline (BL; week 0), post-intervention 1 (P1; week 13) and post-intervention 2 (P2; week 25) and included FES-VO2 measurements, insulin sensitivity and glucose effectiveness using the intravenous glucose tolerance test; anthropometrics and whole and regional body composition assessment using dual energy x-ray absorptiometry (DXA) and magnetic resonance imaging to measure muscle, IMF and VAT CSAs. Results Twenty-seven participants completed both phases of the study. NMES-RT + FES group showed a trend of a greater VO2 peak in P1 [p = 0.08; but not in P2 (p = 0.25)] compared to PMT + FES. There was a time effect of both groups in leg VO2 peak. Neither intervention elicited significant changes in insulin, glucose, or inflammatory biomarkers. There were modest changes in leg lean mass following PMT + FES group. Robust hypertrophy of whole thigh muscle CSA, absolute thigh muscle CSA and knee extensor CSA were noted in the NMES-RT + FES group compared to PMT + FES at P1. PMT + FES resulted in muscle hypertrophy at P2. NMES-RT + FES resulted in a decrease in total VAT CSA at P1. Conclusion NMES-RT yielded a greater peak leg VO2 and decrease in total VAT compared to PMT. The addition of 12 weeks of FES-LEC in both groups modestly impacted leg VO2 peak. The addition of FES-LEC to NMES-RT did not yield additional increases in muscle CSA, suggesting a ceiling effect on signaling pathways following NMES-RT. Clinical trial registration identifier NCT02660073.